THE INFLUENCE OF EMOTIONAL INTELLIGENCE, COMPETENCE AND WORK ENVIRONMENT ON TEACHER PERFORMANCE OF SMP KEMALA BHAYANGKARI JAKARTA - Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The purpose of this study was to determine the effect of emotional intelligence, competence and work environment toward teacher performance either partially or simultaneously. The object research carreid out to the employee stamp of SMP Kemala Bhayangkari Jakarta. Design research conducted in the preparation of this is quantitative that aims to determine the influence between two or more deeply variables describe or reveal a problem, situation, event or revealing fact as they are deeply and try to find a solution or problems solve. The results showed that Emotional intelligence has positive effect on performance with coefficient value of 0.161. Competence has positive effect on performance with coefficient value of 0.429. Work environment positively influence toward performance with coefficient value equal to 0,262. Adjust R Square value of 0.442. Indicates that emotional intelligence, competence and work environment together contribute 44,2% to performance and the rest of 55,8% influenced by other variable outside this research